Economic Analysis of World Bank Education Projects and Project Outcomes - Vawda, Ayesha Yaqub (World Bank, Washington, DC, 2014)
Research reported in this paper tests the hypothesis that Bank education projects for which the project appraisal documents are judged "good" have a higher probability of leading to successful outcomes than projects for which the appraisals are judged "poor." The research draws on project document evaluations carried out between 1993 and 1998. Analysis shows a strong relationship between the quality of cost-benefit and cost-effectiveness analysis and the quality of project outcomes. Economic analysis of projects is a tool for weeding out potentially poor investments and selecting potentially worthwhile ones. The economic analysis can be used to select among alternative projects or to redesign project components so that they yield more and produce better outcomes. Good practice education projects require good economic analysis--analysis of demand, of the counterfactual private sector supply, of the project's fiscal impact, of lending fungibility--and strong sector work before project design.